The impact of border changes and protectionism on real wages in early modern Scania - Kathryn E. Gary; Cristina Victoria Radu (European Historical Economics Society (EHES), 2019)
In the aftermath of Brexit there has been increased speculation into what national borders mean for economic and individual wellbeing. Investigating similar events in history can help us understand some of these potential effects. Malmö, a city in modern-day southern Sweden, was a part of Denmark until the middle of the seventeenth century, located just across the Sound from the capital of Copenhagen. Malmö and its surrounding regions were ceded to Sweden at the end of the Second Northern War in 1658 and Sweden immediately established barriers to trade and to human capital flow between its new territories and Denmark, going so far as to prohibit Swedish attendance to Copenhagen University and instead establishing its own university in Lund in 1666. Malmö and its surrounding region, Scania, quickly shifted from an important trade city located within sight of the capital to a distant periphery with limited trade capacity. This change in possession of Scania provides a historical experiment that can highlight the effect of the second nature geography changes as well as protectionism on well-being. We use a novel database of Danish and Swedish real wages to investigate the impact of these changes on Scanian living standards by employing a difference in difference approach to show that wages fell more in Scania than those in surrounding regions in relation to the border change and associated protectionism.
Keywords: J31; N33; N93; 330; Border Changes; Real Wages; Second Nature Geography; Welfare Ratios; Standard of Living; Denmark; Sweden; Malmo; Scania; Scandinavia; Early Modern Period